Juvenile arrest in America : race, social class, and gang membership - Tapia, Mike, 1974- (Criminal justice (LFB Scholarly Publishing LLC), 2012)
Tapia studies how race, social class, and gang membership interact to shape arrest patterns for American youth. With differences in delinquency level controlled for the various subgroups of youth in the study, a critical test of labeling theory is executed. Modeling how social class and gang membership condition race effects lends more clarity to the contours of arrest risk for America?s youth. Gang membership and social class also interact in surprising and interesting ways. Some findings are paradoxical, even counterintuitive. The insights obtained will inform the ongoing federal research in.